Effects of chromium histidinate supplementation on insulin sensitivity and lipid profile in rat models of insulin resistance and of type 2 diabetes - Juturu, Vijaya; Kazim, Sahin; Tuzcu, Mehmet; Cikim, Gurkan; Komorowski, James R. (Federation Amer Soc Exp Biol, 2008)
[Abstract Not Available]